NOD2 (Nucleotide-Binding Oligomerization Domain 2) Is a Major Pathogenic Mediator of Coxsackievirus B3-Induced Myocarditis. (September 2017) - Tschöpe, Carsten; Müller, Irene; Xia, Yu; Savvatis, Konstantinos; Pappritz, Kathleen; Pinkert, Sandra; Lassner, Dirk; Heimesaat, Markus M.; Spillmann, Frank; Miteva, Kapka; Bereswill, Stefan; Schultheiss, Heinz-Peter; et al.
Abstract : Background: The cytoplasmatic pattern recognition receptor, NOD2 (nucleotide-binding oligomerization domain 2), belongs to the innate immune system and is among others responsible for the recognition of single-stranded RNA. With Coxsackievirus B3 (CVB3) being a single-stranded RNA virus, and the recent evidence that the NOD2 target, NLRP3 (NOD-like receptor family, pyrin domain containing 3) is of importance in the pathogenesis of CVB3-induced myocarditis, we aimed to unravel the role of NOD2 in CVB3-induced myocarditis. Methods and Results: Endomyocardial biopsy NOD2 mRNA expression was higher in CVB3-positive patients compared with patients with myocarditis but without evidence of persistent CVB3 infection. Left ventricular NOD2 mRNA expression was also induced in CVB3-induced myocarditis versus healthy control mice. NOD2 knockdown (−/− ) mice were rescued from the detrimental CVB3-mediated effects as shown by a reduced cardiac inflammation (less cardiac infiltrates and suppression of proinflammatory cytokines), cardiac fibrosis, apoptosis, lower CAR (Coxsackievirus and adenovirus receptor) expression and CVB3 copy number, and an improved left ventricular function in NOD2 −/− CVB3 mice compared with wild-type CVB3 mice. In agreement, NOD2 −/− decreased the CVB3-induced inflammatory response, CVB3 copy number, and apoptosis in vitro. NOD2 −/− was further associated with a reduction in CVB3-induced NLRP3 expression and activity as evidenced by lower ASC (apoptosis-associated speck-like protein containing a CARD) expression, caspase 1 activity, or IL-1β (interleukin-1β) protein expression under in vivo and in vitro CVB3 conditions. Conclusions: NOD2 is an important mediator in the viral uptake and inflammatory response during the pathogenesis of CVB3 myocarditis. Abstract : Supplemental Digital Content is available in the text.